Multifunctional copper dimer: structure, band gap energy, catalysis, magnetism, oxygen reduction reaction and proton conductivity - Sarkar, D.; Chandra Rao, P.; Aiyappa, H. B.; Kurungot, S.; Mandal, S.; Ramanujam, K.; Mandal, S. (RSC Advances, 2016)
A new dimeric copper complex namely, [Cu2(PDA)2(Ald)2(H2O)2]·8H2O, 1, (where PDA = 2,4-pyridine dicarboxylic acid, Ald = aldrithiol) has been synthesized through a slow diffusion technique. Compound 1 is a molecular structure and assembled through H-bonding forming a supramolecular architecture. The CuO2N3 units bridged through an aldrithiol molecule to form the dimeric structure. The lattice water molecules are linked through H-bonding to form the decameric water cluster. The decameric water clusters are H-bonded to each other to form the 1D chain which resulted in excellent water stability and conduction of protons under humid conditions. Band gap energy and magnetic measurements show that compound 1 is a semiconductor and paramagnetic in nature. Further the compound is shown as a selective heterogeneous catalyst for styrene and cyclohexene epoxidation. This also shows a facile oxygen reduction reaction (ORR) and can be used as a promising Pt-free cathode in alkaline Direct Methanol Fuel Cells (DMFC). The present results suggest that compound 1 is a promising multifunctional material